The functional organization of the left STS: a large scale meta-analysis of PET and fMRI studies of healthy adults - Liebenthal, Einat; Desai, Rutvik H.; Humphries, Colin; Sabri, Merav; Desai, Anjali (Frontiers in Neuroscience, 2014)
The superior temporal sulcus (STS) in the left hemisphere is functionally diverse, with sub-areas implicated in both linguistic and non-linguistic functions. However, the number and boundaries of distinct functional regions remain to be determined. Here, we present new evidence, from meta-analysis of a large number of positron emission tomography (PET) and functional magnetic resonance imaging (fMRI) studies, of different functional specificity in the left STS supporting a division of its middle to terminal extent into at least three functional areas. The middle portion of the left STS stem (fmSTS) is highly specialized for speech perception and the processing of language material. The posterior portion of the left STS stem (fpSTS) is highly versatile and involved in multiple functions supporting semantic memory and associative thinking. The fpSTS responds to both language and non-language stimuli but the sensitivity to non-language material is greater. The horizontal portion of the left STS stem and terminal ascending branches (ftSTS) display intermediate functional specificity, with the anterior ascending branch adjoining the supramarginal gyrus (fatSTS) supporting executive functions and motor planning and showing greater sensitivity to language material, and the horizontal stem and posterior ascending branch adjoining the angular gyrus (fptSTS) supporting primarily semantic processing and displaying greater sensitivity to non-language material. We suggest that the high functional specificity of the left fmSTS for speech is an important means by which the human brain achieves exquisite affinity and efficiency for native speech perception. In contrast, the extreme multi-functionality of the left fpSTS reflects the role of this area as a cortical hub for semantic processing and the extraction of meaning from multiple sources of information. Finally, in the left ftSTS, further functional differentiation between the dorsal and ventral aspect is warranted.